2018
DOI: 10.1108/jkm-09-2017-0391
|View full text |Cite
|
Sign up to set email alerts
|

Improving innovation performance through knowledge acquisition: the moderating role of employee retention and human resource management practices

Abstract: Purpose This paper aims to study the effects of knowledge acquisition on innovation performance and the moderating effects of human resource management (HRM), in terms of employee retention and HRM practices, on the above-mentioned relationship. Design/methodology/approach A sample of 129 firms operating in a wide array of sectors has been used to gather data through a standardized questionnaire for testing the hypotheses through ordinary least squares (OLS) regression models. Findings The results indicate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
225
2
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 315 publications
(293 citation statements)
references
References 110 publications
17
225
2
6
Order By: Relevance
“…It must be noted that the focus of knowledge-based companies on knowledge flows and technologic processes are the most important elements in gaining competitive advantage [82] and a sustainable balanced performance. With respect to the results obtained from examination of the second hypothesis, it could be said that results of this test are in line with results of other research [83][84][85]. Based on the observations made by researchers in this this industry, it is suggested that knowledge-based companies help their organizations by improving innovation in conscious management activities and creating target internal groups.…”
Section: Resultssupporting
confidence: 83%
“…It must be noted that the focus of knowledge-based companies on knowledge flows and technologic processes are the most important elements in gaining competitive advantage [82] and a sustainable balanced performance. With respect to the results obtained from examination of the second hypothesis, it could be said that results of this test are in line with results of other research [83][84][85]. Based on the observations made by researchers in this this industry, it is suggested that knowledge-based companies help their organizations by improving innovation in conscious management activities and creating target internal groups.…”
Section: Resultssupporting
confidence: 83%
“…According to the research of Andreeva et al [51], the knowledge process and knowledge intensity have a positive impact on innovation. Research of Papa et al [52] proves that external knowledge acquisition has a positive impact on innovation performance in the context of open innovation.…”
Section: External Knowledge Acquisition and Environmental Innovationmentioning
confidence: 99%
“…Many scholars claim that organizations should value the high levels of tacit and personal knowledge that many people have, and it should be down to HRM to build effectively a good level of loyalty and retention rates [39]. Papa et al [66] found that employee retention improves the effect of knowledge acquisition and innovation performance. They explained that employee retention increases employee commitment and trust, thus fostering knowledge specialization and fortification and creating an innovation culture.…”
Section: Knowledge-based Retention Managementmentioning
confidence: 99%